Electroconductive natural polymer-based hydrogels. (December 2016) - Shi, Zhijun; Gao, Xing; Ullah, Muhammad Wajid; Li, Sixiang; Wang, Qun; Yang, Guang
Abstract: Hydrogels prepared from natural polymers have received immense considerations over the past decade due to their safe nature, biocompatibility, hydrophilic properties, and biodegradable nature. More recently, when treated with electroactive materials, these hydrogels were endowed with high electrical conductivity, electrochemical redox properties, and electromechanical properties; consequently, forming a smart hydrogel. The biological properties of these smart hydrogels, classified as electroconductive hydrogels, can be combined with electronics. Thus, they are considered as good candidates for some potential uses, which include bioconductors, biosensors, electro-stimulated drug delivery systems, as well as neuron-, muscle-, and skin-tissue engineering. However, there is lacking comprehensive information on the current state of these electroconductive hydrogels which complicates our understanding of this new type of biomaterials as well as their potential applications. Hence, this review provides a summary on the current development of electroconductive natural polymer-based hydrogels (ENPHs). We have introduced various types of ENPHs, with a brief description of their advantages and shortcomings. In addition, emerging technologies regarding their synthesis developed during the past decade are discussed. Finally, two attractive potential applications of ENPHs, cell culture and biomedical devices, are reviewed, along with their current challenges.